Translating Labor History for Television - Cox, Pamela (2019)
This article considers the challenges and advantages of translating academic historical research into popular television formats. It traces key moments in the development of televised history programmes in Britain from the 1950s to the present and explores the impact of two signiicant recent shifts: the fragmentation of traditional academic expertise; and the empowerment of audiences. The article moves on to discuss how these and other shifts helped to shape the making of two major BBC history series on women’s labor, both presented and co-written by the author (Servants, 2012 and Shopgirls, 2014). This article is adapted from a keynote address by the author to the Worlds of Labor conference in Porto Alegre in 2018.Translating Labor History for Television